Antitumor effects and potential mechanisms of aconitine based on preclinical studies: an updated systematic review and meta-analysis - Xiang, Gelin; Xing, Nan; Wang, Shaohui; Zhang, Yi (Frontiers in Pharmacology, 2023)
Background: Herbs originating from the Aconitum L. (Ranunculaceae), such as Aconitum carmichaelii Debeaux. (Wutou), Aconitum pendulum Busch. (Tiebangchui), and Aconitum kusnezoffii Reichb. (Caowu), etc. are highly valued for their medicinal properties. The roots and tubers of these herbs are commonly used to treat an array of ailments, including joint pain and tumors. The alkaloids present in them are the primary active components, with aconitine being the most notable. Aconitine has gained attention for its exceptional anti-inflammatory and analgesic properties, as well as its potential as an anti-tumor and cardiotonic agent. However, the exact process through which aconitine hinders the growth of cancerous cells and triggers their programmed cell death remains unclear. Therefore, we have undertaken a comprehensive systematic review and meta-analysis of the current research on the potential antitumor properties of aconitine. Methods: We conducted a thorough search of relevant preclinical studies in databases including PubMed, Web of Science, VIP, WanFang Data, CNKI, Embase, Cochrane Library, and National Center for Biotechnology Information. The search was conducted up until September 15, 2022, and the data were statistically analyzed using RevMan 5.4 software. The number of tumor cell value-added, tumor cell apoptosis rate, thymus index, and Bcl-2 gene expression level were the main indicators to be analyzed. Results: After applying the final inclusion criteria, a total of thirty-seven studies, comprising both in vivo and in vitro research were analyzed. The results showed that treatment with aconitine led to a significant reduction in tumor cell proliferation, a noteworthy increase in the rate of apoptosis among tumor cells, a decrease in the thymus index, and a reduction in the expression level of Bcl-2. These results suggested that aconitine could inhibit the proliferation, invasion, and migration abilities of tumor cells by regulating Bcl-2 etc., thereby enhancing the anti-tumor effects. Conclusion: In summary, our present study demonstrated that aconitine effectively reduced tumor size and volume, indicating a strong anti-tumor effect. Additionally, aconitine could increase the expression levels of caspase-3, Bax and other targets. Mechanistically, it may regulate the expression levels of Bax and Bcl-2 through the NF-κB signaling pathway, ultimately inhibiting tumor cell proliferation through autophagy.